BIODIVERSITY DISCLOSURE OF INDONESIAN COMPANIES AND THE ROLE OF THE BOARD OF COMMISSIONERS - Hambali, Ahmad; Adhariani, Desi (UI Scholars Hub, 2022)
The environmental damage that occurs on a large scale has an impact on reducing biodiversity. Biodiversity has an important role that is useful for human life and plays a central role in economic development. This condition makes various parties aware of their role in preventing further damage. Companies, whether directly or indirectly, owe a great deal to the environment. This study seeks to examine the role of the Board of Commissioners as proxied by the size of the Board of Commissioners, the proportion of Independent Boards, and the proportion of women on the Board of Commissioners as a corporate governance mechanism for their biodiversity disclosure. The companies used as samples are listed in the SRI-KEHATI index from 2018 to 2020. To measure the company's biodiversity variable, we use a biodiversity index which contains 53 measurement items in 5 main themes. As a result, we find that the size of the Board of Commissioners has a positive effect on the company's biodiversity disclosure. Meanwhile, the proportion of Independent Commissioners and the proportion of women on the Board of Commissioners are proven to have no effect on the company's biodiversity disclosure.